Binary Fe, Cu-doped bamboo-like carbon nanotubes as efficient catalyst for the oxygen reduction reaction. (July 2017) - Fan, Wenjun; Li, Zelong; You, Chenghang; Zong, Xu; Tian, Xinlong; Miao, Shu; Shu, Ting; Li, Can; Liao, Shijun
Abstract: In this work, CuCl2 as a promoter was added into the mixture of polythiophene (PTh), FeCl3, and melamine for preparing Fe-Cu-N/C catalyst. The catalyst features one-dimensional bamboo-like carbon nanotubes with few metal oxide nanoparticles encapsulated into tubes. The catalyst exhibits excellent activity toward the oxygen reduction reaction (ORR) with half-wave potential 50 mV more positive than the commercial Pt/C in 0.1 M KOH. It also shows comparable ORR activity in 0.1 M HClO4 solution. Moreover, it exhibits superior long-term stability and excellent methanol tolerance in both alkaline and acidic solutions. The outstanding catalytic performance of Fe-Cu-N/C catalyst can be ascribed to the doping of Cu in the Fe-N-C architecture, which promotes the formation of bamboo-like nanotube structure and the generation of interaction among Cu and Fe-N-C. This synthetic strategy may open new avenues for constructing highly efficient electrocatalysts that adding of an inactive metal can obviously promote the catalytic performance of catalysts. Graphical abstract: Highlights: Binary Fe- and Cu-codoped carbon nanotubes was proposed as efficient catalyst for ORR. The Fe-Cu-N/C catalyst exhibits uniform bamboo-like morphology, high surface area and hierarchical porous structure. The doping of Cu into Fe-N-C architecture was found to effectively tune the electronic structure. The Fe-Cu-N/C catalyst exhibits superior activity and stability to commercial Pt/C in 0.1 M KOH and HClO4 solution.